Attitudinal Messages in the Friday Sermon on Death: Appraisal Analysis - Dias Andris Susanto (ETERNAL (English Teaching Journal), 2023)
Abstract. Friday sermons are the most significant speeches in the Muslim world and have been for years, they are the least critically investigated in the science of discourse analysis. The primary goals of this study were to investigate the attitudinal resources in the Friday Sermon on Death and to figure out the most attitudinal resources are revealed how sermon meanings are constructed in the Friday Sermon on death. This study falls into the category of descriptive qualitative research. The data comes in the form of text, which comprises attitudes, and it is these attitudes that are being investigated in this study. This study concentrated on attitudinal resources in the appraisal theory. The transcript of Friday sermon data for this enquiry was obtained from the Navedz.com website on March 27, 2009. It was determined that the preacher Al-Madinah Al- Munawwarrah 'Abdul Ibn 'Awad Ath-Thubayti established himself with 23 Affect clausesÂ with a percentage of 39 percent.Â  Judgement is linked to 29 sentences in the Friday sermon, then according to the findings, the preacher used appreciation resources in 7 clauses.Â